A Pathway To Adapt Hybrid Learning For Pre-Service Teachers As The New Normal In Curriculum Practice: Using Whatsapp As A Learning Tool - Mphuthi, Mochina; Tshelane, Molaodi (My University, 2022)
The use of hybrid learning in curriculum practices to improve teaching and learning a recent initiatives in the package pedagogical reforms in South Africa. Nowadays, an increasing number of students have their own smartphones, and WhatsApp is becoming popular in terms of mobile learning and communication .WhatsApp is an application that can be used by students in post-secondary education to improve performance, and motivation to prepare for their learning . This article reflects on a pathway followed by pre-service economic and management sciences (EMS) teachers in their ability to adapt and sustain their learning through WhatsApp as a hybrid learning tool. The study is underpinned by connectivism theory. Qualitative research using Participatory Action Learning and Action Research (PALAR) approach as a form of critical education science is employed in research methodology and design . Semi structured Interviews were conducted with 30 Pre-Service EMS teachers to generate data. PALAR is relevant to the study as it pilgrimages three principles of responsible research innovations such as recognition of participants, establishing professional learning communities and critical reflections embracing diversity characterised in unequal education context in the South Africa. Critical discourse analysis was used to arrive at the finding that depicts close 96% of the participants are inclined to use WhatsApp as a learning tool as 84% had reliable access to Wi-Fi on campus. The paper concludes with recommendations that the hybrid learning is the future of teaching and learning in post Covid era and should be embraced .
Keywords: Pre-service teachers; Hybrid learning; Curriculum practice .connectivism; WhatsApp